(untitled) (Journal of Humanities and Social Sciences Research, 2023)
The study aims to create a strategic vision for the criteria for determining instructional techniques in order to improve the performance of physical education instructors in schools, youth organizations, and sports organizations. The parameters impacting the selection of acceptable teaching techniques for physical education instructors in schools, youth organizations, and sports clubs were determined. The descriptive approach was chosen by the researcher due to its fit for achieving the research’s purpose, the research community, and the research sample. The research community consists of physical education instructors from the Babylonian provinces. The researcher gathered the study sample at random, which consisted of (186) persons, and after distributing the questionnaire, the inaccurate questionnaires were eliminated, resulting in the research sample reaching (170) individuals. In order to examine the obtained data, the researcher employed the Spss statistical software tool. In other hand, descriptive statistical methods were used to compute the arithmetic mean, standard deviation, and Skewness coefficients for the study sample’s replies to the final version of the questionnaire. The researcher reached the conclusion that it was produced by a set of criteria. - The first criterion (teaching competency) was satisfied with (8) phrases, and the factorial variance % for the satiated phrases was (51,711), which is deemed the largest variance percentage for the extracted criteria. The second requirement (technique) was fulfilled with (8) expressions, and the percentage of factorial variance for the satiated expressions was calculated. (10,013). - With (8) expressions, the third condition (method) was satisfied, and the proportion of the factorial variance for the satiated phrases was calculated. (6,546). The researcher presented a number of recommendations: • Benefit from the vision attained while selecting current teaching techniques in educational institutions, youth organizations, and sports organizations to raise performance levels. • Developing criteria for selecting current teaching techniques that are distinguished by the ability to handle change, development, and innovation in the inventive personality, as well as the ability to successfully manage the lesson. - The aim of the search: The research intends to provide a strategic vision of criteria for selecting instructional techniques in order to improve the effectiveness of physical education instructors in schools, youth organizations, and sports organizations through: • Identifying the characteristics that impact the selection of effective teaching techniques for physical education teachers in schools, youth organizations, and sports organizations. Search Queries: The researcher answers the following questions in light of the study objective: 1- What are the influencing criteria for determining instructional approaches to improve teacher performance in schools, youth, and sports organizations? 2- What is the strategic aim for the criteria for selecting instructional approaches to enhance teacher performance in schools, youth organizations, and sports organizations?